P PERAN ORANG TUA MENSTIMULASI PERKEMBANGAN ANAK DENGAN STATUS PERKEMBANGAN ANAK USIA 3-5 TAHUN DI POLI ANAK RSUD PAMBALAH BATUNG - Hinderayani, Nani; Ariani, Malisa; Basit, Mohammad (LPPM Universitas Sari Mulia, 2023)
Background: Every stage of a child's growth and development is very important in the first thousand Days of Life (HPK) of his birth. Parental care and upbringing greatly affects the stage of its development. Proper stimulation will stimulate the child's brain so that its development becomes optimal. Objective: The aim of the study was to analyze the relationship between the role of parents in stimulating children's development and the developmental status of children aged 3-5 years at the Children's Polyclinic at Pambalah Hospital, Batung. Method: This study uses the Cross Sectional method. The population of parents and their children aged 3-5 years who visited the Children's Polyclinic at Pambalah Batung Hospital, the number of samples was 54 people. Purposive Sampling Technique. Questionnaire instruments and observation sheets and using the Chi Square test. Result: The results showed that the role of stimulating good child development was 43 people (79.6%), the appropriate child development status was 34 people (63%). There I s a significant relationship with a value (p value) of 0.022, where the p value α (≤ 0.05). Conclusion: Parents with a good role in stimulating the chance to have children with appropriate development compared to parents with a role that is not good in stimulating.